Novel evaluation of In vitro Anti-inflammatory and Free Radical Scavenging activities of Ficus krishnae - Londonkar, Ramesh L (International Journal of Pharmaceutical & Biological Archive, 2018)
Ficus krishnae also known as â€œMakkhankathorâ€ belongs to family Moraceae and is reported to be highlymedicinal in India. As a folk medicine, the plant is used in treatment of broad range of diseases anddisorders. In the present study the methanol and aqueous extracts of Ficus krishnae was evaluated for itstotal phenolic, Flavonoid content, in vitro anti-inflammatory and free radical scavenging activity of Ficuskrishnae. Invitro anti-inflammatory activity by inhibition of protein denaturation method and antioxidantpotential of extract was carried out by free radical scavenging activity using 2, 2 diphenyl 1-picrylhydrazyl (DPPH), ABTS radical scavenging activity, reducing power assay and phosphomolybdenumassay by using ascorbic acid and BHT as reference standards. Total phenol and flavonoid content ofmethanol extracts found to be 0.34mg/g and 0.60mg/g. whereas aqueous extract was to be 0.14mg/g and0.10mg/g. Invitro anti-inflammatory study of polar solvent extracts has showed that the crude methanolextract of F.krishnae is a potential source of natural inhibition of protein denaturation and antioxidantsthis justified its uses in folkloric medicine.